Clinical characteristics of patients with Human Immunodeficiency Virus. Enrique Cabrera General Teaching Hospital - Dinorah de la Caridad Oliva Venereo; Bladimir Rodríguez Benavides; Arturo Luís Viñas Martínez; Jorge Luis Valdés Fuster; Yunier Andrés Camilo Cuellar (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: The care of patients with Human Immunodeficiency Virus is currently carried out in a decentralized way in Cuba. The number of patients with HIV admitted to general hospitals is increasing. Objective: To determine the clinical characteristics of patients with HIV admitted to Enrique Cabrera General Teaching Hospital. Material and Methods: A descriptive retrospective study was carried out in patients with HIV admitted to Enrique Cabrera General Teaching Hospital from January 1st, 2007 to December 31st, 2013. The sample consisted of 86 cases. Results: The number of patients increased per year, male cases constituted 79 %, the most frequent age groups were from 21 to 30 years and from 41 to 50 years. Generalized adenopathies were the most frequent findings on physical examination. CD4 T- cell counts below 200 cells/mm3 predominated in the study. Respiratory pathologies constituted 25 % of the causes of admission. Hospital diagnosis was carried out in 36 % of the cases, 77 % of which had late diagnoses of HIV. Conclusions: HIV patients constitute a young population that is admitted more and more to secondary level hospitals.  They present own characteristics of the disease and pathologies that put their lives at risk. Keywords: HIV, AIDS, generalized adenopathies, CD4 T-cell count, hospital diagnoses, late diagnosis, AIDS case.